The Correlation Between the Number of Vascular Risk Factors and The Onset of Hemodialysis with Cognitive Impairement in Chronic Kidney Disease (CKD) Patients - Priyanka Ganesa Utami; Wiwin Sundawiyani (Magna Neurologica, 2024)
Background: Cognitive impairment is a common disorder in patients with chronic kidney disease (CKD). At least, 50% of CKD patients experience impaired cognitive function caused by ischemia associated with impaired vascular function. In addition, significant changes during the dialysis process such as loss of water and ultrafiltration will disrupt the blood supply to the brain and exacerbate ischemia that underlies the incidence of impaired cognitive function. Objective: Analyze the correlation between vascular risk factors, dialysis onset, and cognitive impairment in CKD patients. Methods: This analytic observational study sampled CKD patients on hemodialysis between February-July 2023, using purposive sampling. Inclusion and exclusion criteria were applied, and cognitive function was assessed using MOCA-INA. Spearman's rho statistical analysis was employed at a 95% confidence level (p <0.05). Results: The results of correlation test using Spearman Rho showed patients undergoing hemodialysis for more than 5 years had a correlation with impaired cognitive function, P=0.02. Cognitive domains that are most affected sequentially are memory/delayed recall, visuospatial, abstraction, language, attention and naming. While the number of vascular risk factors did not have a correlation with cognitive impairment with P=1.38. Conclusion: CKD patients on hemodialysis for more than 5 years show a correlation with impaired cognitive function, primarily affecting memory/delayed recall, visuospatial, abstraction, language, attention, and naming. Vascular risk factors, however, exhibit no correlation with cognitive impairment.